Transmission-blocking activities of quinine, primaquine, and artesunate. - Chotivanich, K; Sattabongkot, J; Udomsangpetch, R; Looareesuwan, S; Day, N; Coleman, R; White, N (2006)
The infectivity of Plasmodium falciparum gametocytes after exposure in vitro to quinine, artesunate, and primaquine was assessed in Anopheles dirus, a major vector of malaria in Southeast Asia. Mature gametocytes (stage 5) of a Thai isolate of P. falciparum were exposed to the drugs for 24 h in vitro before membrane feeding to A. dirus. After 10 days, the mosquito midguts were dissected and the oocysts were counted. In this system, artesunate showed the most potent transmission-blocking activity; the mean (standard deviation [SD]) 50% and 90% effective concentrations (EC(50), and EC(90), respectively, in nanograms per milliliter) were 0.1 (0.02) and 0.4 (0.15), respectively. Transmission-blocking activity of quinine and primaquine was observed at relatively high concentrations (SDs): EC(50) of quinine, 642 (111) ng/ml; EC(50) of primaquine, 181 (23) ng/ml; EC(90) of quinine, 816 (96) ng/ml; EC(90) of primaquine, 543 (43) ng/ml. Artesunate both prevents the maturation of immature P. falciparum gametocytes and reduces the transmission potential of mature gametocytes. Both of these effects may contribute to reducing malaria transmission.